Contemporary avenues in catalytic P-H bond addition reaction: a case study of hydrophosphination - Koshti, Vijay; Gaikwad, Shahaji R.; Chikkali, Samir H. (Coordination Chemistry Reviews, 2014)
Remarkable advances and current state-of-the-art developments in catalytic hydrophosphination of alkenes and alkynes are reviewed. The challenges in constructing a C P bond with a special emphasis on metal catalysed (asymmetric) hydrophosphination are highlighted. Only those systems that unambiguously proceed via P H bond addition across a C-C/X (X = O, N, S) multiple bond have been covered in this overview. Reviewed examples support the assumption that either strongly chelating ligands or reaction products that act as ligands, enhance the rate of hydrophosphination. The asymmetric variant of this transformation allows installation of p-chiral [enantiomeric excess (ee) up to 82%] as well as C-chiral (ee up to 99%) centres. The limited spectroscopic, mechanistic data and OFT calculations point at two distinctly different mechanisms. In case of hydrophosphination, the metal undergoes oxidative addition and reductive elimination steps (in general), thus changing the oxidation state from M(0) to M(II) and back to M(0). Whereas in asymmetric hydrophosphination it is proposed that the oxidation state of the metal remains unaltered throughout the catalytic cycle. The examples described in this overview showcase the real power of catalytic hydrophosphination in constructing various phosphorus compounds, which may initiate a new era in organo-phosphorus chemistry. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alkynes; Asymmetric hydrophosphination; Hydrophosphination; Metal catalyzed hydrophosphination; Olefins; P-H bond addition

Iron in organometallic transformations: a sustainable substitute for noble metals - Kumar, Rohit; Tewari, Tanuja; Chikkali, Samir H. (ChemCatChem, 2024)
Transition metal catalysis plays a pivotal role in chemical synthesis. Noble metals often grab significant attention in organometallic catalysis due to their high reactivity. However, the serious issues associated with these metals such as low abundance, toxicity, geopolitical limitations, and volatile prices are driving the scientific community to discover sustainable alternatives. In this context, iron appears to be the first choice as an alternative metal due to its unique properties, including a range of stable oxidation states, Lewis acidity, high abundance in the earth's crust, and low toxicity. Over the past two decades, substantial progress has been made in iron catalysis. This overview examines the recent developments in iron-catalyzed industrially relevant transformations such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. As witnessed throughout this review, the performance of iron can be significantly altered by suitable ligand selection and by tailoring the electronic and steric properties of the iron center. While noble metals remain the industry work-horse, iron is inching closer and with extensive scientific understanding, it may replace noble metals in the near future. Late transition metals catalyze several reactions and have been the industry work-horse for decades. While, earth abundant metals are rarely used in industrially relevant transformations. In this overview, we examine the recent development in iron-catalyzed industrially relevant reactions such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. Iron is inching closer and may replace noble metals in near future. image
Keywords: Alkene Isomerization; alkyne; Carbonylation; depolymerization; Hydrophosphination; Hydrosilylation; iron catalysis

P-chiral organophosphorus compounds: synthesis, mechanism, and applications - Chandanshive, Amol C.; Chikkali, Samir H. (Chemistry-an Asian Journal, 2026)
The enantioselective synthesis of P-stereogenic compounds has emerged as a central focus in modern asymmetric catalysis, driven by their pivotal roles as ligands (Ls), organocatalysts, and bioactive molecules. Over the past decade, significant advances have been made in developing catalytic strategies that enable precise control over phosphorus stereochemistry, expanding both the structural diversity and synthetic utility of these scaffolds. This review highlights recent progress in two key areas: direct P-C bond formation and desymmetrization. P-C bond-forming approaches include cross-coupling reactions of secondary phosphines or their oxides with aryl, alkyl, or benzyl halides, as well as hydrophosphination of alkenes and alkynes. Desymmetrization strategies encompass nucleophilic substitution at P(V) centers, cyclization, C-H activation (CHA), phenolic -OH activation, and P-O alkylation/arylation. Mechanistic insights into these transformations have been discussed, along with the derivatization of P-chiral products and their applications in catalysis, L design, and bioactive molecule synthesis. This comprehensive overview shall serve as a valuable resource for researchers working in asymmetric organophosphorus chemistry.
Keywords: desymmetrization; Hydrophosphination; P-C cross coupling; P-chiral phosphines; phosphination